2002
DOI: 10.1161/01.str.0000020355.29423.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Gadolinium-DTPA on Diffusion-Weighted Images

Abstract: Background and Purpose-Diffusion-weighted imaging (DWI) is usually done before administration of intravenous contrast agents. Repetition of DWI is occasionally necessary after administration, but the effects of contrast material on DWI and apparent diffusion coefficient (ADC) values have not yet been fully examined. The present study assesses whether administration of gadolinium-based contrast material significantly affects DWI and ADC values. Methods-We examined DWI data from 39 patients (mean age, 67.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 14 publications
3
43
1
1
Order By: Relevance
“…Our own phantom experiments (see supplemental material 1) on Gd-DTPA solutions of 0.05 -7 mmol/l did not show a significant influence on the DWI technique used in the expected Gd-DTPA concentration. This finding is backed up by several experimental and clinical studies using a physically comparable EPI-DWI technique in Gd-enhancing lesions [29][30][31]. A recent investigation on breast DWI reported a contrast medium influence on ADC measurements.…”
Section: Discussionmentioning
confidence: 82%
“…Our own phantom experiments (see supplemental material 1) on Gd-DTPA solutions of 0.05 -7 mmol/l did not show a significant influence on the DWI technique used in the expected Gd-DTPA concentration. This finding is backed up by several experimental and clinical studies using a physically comparable EPI-DWI technique in Gd-enhancing lesions [29][30][31]. A recent investigation on breast DWI reported a contrast medium influence on ADC measurements.…”
Section: Discussionmentioning
confidence: 82%
“…Detection of a malignant tumour is based on the increase in signal intensity on DWI, and discrimination between benign and malignant tumours is based on the apparent diffusion coefficient (ADC). However, several factors may alter the ADC (7)(8)(9)(10)(11). Iodinated contrast agents are predicted to affect the ADC due to their high viscosity and large molecular size.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies dealing with the influence of CM on the ADC value of normal brain tissue and infarcts. Yamada et al found a significant decrease of the ADC value after CM administration [20], while there was no difference in the study of Fitzek et al [21]. In the study of Yamada et al, DWI was obtained immediately after CM application, while there was a longer time interval in the study of Fitzek et al Firat et al combined both protocols and found a significant decrease of the ADC value of normal brain tissue and infarct immediately after CM application which normalized in the late post-contrast DW images [22].…”
mentioning
confidence: 98%